Framework for Deploying Web Trustability in Cloud Environment - Singh, Amanpreet; Kaur, Amandeep; Gupta, Deepali (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Cloud Computing is an online strategy for the dynamic allocation of services by reducing the use of hardware and software resources. Existing models of cloud computing include different components: end-user computers, contact networks, access control frameworks, and software infrastructures. In a cloud environment, one needs to design a framework that calculates trustability. This paper focuses on the different web page components that make the current cloud computing framework more trustworthy. Any website becomes more trustable when the total load time of the web page is less, and the website becomes more secure with the Hypertext Transfer Protocol Secure protocol. In this paper, a new framework has been proposed and deployed in a cloud environment to ensure web trustability. This research showed that page load time was reduced by up to an average of 9.92 seconds when comparing the performance of different websites through the proposed algorithms. A comparison has been made of trustability factors among different websites with various threshold values.